The protein encoded by the Drosophila position-effect variegation suppressor gene Su(var)3-9 combines domains of antagonistic regulators of homeotic gene complexes. - Tschiersch, B.; Hofmann, A.; Krauss, V.; Dorn, R.; Korge, G.; Reuter, G. (The EMBO Journal, 1994)
Modifier mutations of position-effect variegation (PEV) represent a useful tool for a genetic and molecular dissection of genes connected with chromatin regulation in Drosophila. The Su(var)3-9 gene belongs to the group of haplo suppressor loci which manifest a triplo enhancer effect. Mutations show a strong suppressor effect even in the presence of PEV enhancer mutations, indicating a central role of this gene in the regulation of PEV. By molecular analysis, Su(var)3-9 could be correlated with a 2.4 kb transcript which encodes a putative protein of 635 amino acids containing a chromo domain and a region of homology to Enhancer of zeste and trithorax, two antagonistic regulators of the Antennapedia and Bithorax gene complexes, as well as to the human protein ALL-1/Hrx which is implicated in acute leukemias. This region of homology is found in all four proteins at the C-terminus. The homology of Su(var)3-9 to both negative (Polycomb and Enhancer of zeste) and positive (trithorax) regulators of the Antennapedia and Bithorax complexes also suggests similarities in the molecular processes connected with stable transmission of a determined state and the clonal propagation of heterochromatinization.